Optimized repetitive sampling X-bar control chart: performance evaluation and comparison with Shewhart control chart - Muñoz, Jose J.; Aslam, Muhammad; Campuzano, Manuel J. (Frontiers in Applied Mathematics and Statistics, 2023)
When initial sample information falls short of enabling industrial engineers to confidently make decisions about lot quality assessment, repetitive sampling emerges as a solution.Within this manuscript, we present an optimized repetitive sampling control chart for X-bar values. Through meticulous analysis, we determine the optimal control chart coefficients.Additionally, we establish the control chart parameters for scenarios where the sample size equals the average sample number, encompassing both in-control and out-of-control processes. To underscore the effectiveness of our proposed chart compared to the traditional Shewhart control chart, we furnish comprehensive tables across various sample sizes. By meticulously examining these tables alongside the corresponding control charts, the chart's efficacy in relation to the Shewhart alternative becomes evident.